Wrapping Drugs in Butter : Developing a New Oral Delivery System for Amphotericin B - Hodgson, Shane; Heimann, Joseph; Wiltgen, Hilary E. (My University, 2013)
One of the most common serious diseases of the developing world is almost unknown in this country. It is Leishmanaisis, also known as kalaazar. After malaria, this is the most common fatal parasitic infection in the world. It is difficult to treat and has demonstrated increasing rates of resistance toward many main-line drugs. Fortunately, there is a drug which is very effective, almost never generates resistance and is very inexpensive--Amphotericin B (AmB). The problem is that this drug is not available in a stable oral form which would be advantageous in tropical climates. The purpose of this study was to develop and establish procedures for testing and characterization of novel orally-available lipid drug delivery formulas for AmB.
Color poster with text, photographs, charts, images, and graphs.
Keywords: Leishmaniasis--Treatment of; Posters; Amphotericin B--Administration of